Biomarkers of PEGylated Liposomal Doxorubicin-Induced Hypersensitivity Reaction in Breast Cancer Patients Based on Metabolomics - Zhuang, Wei; Lai, Xiuping; Mai, Qingxiu; Ye, Suiwen; Chen, Junyi; Liu, Yanqiong; Wang, Jingshu; Li, Siming; Huang, Yanqing; Qin, Tao; Hu, Hai; Wu, Junyan; et al. (Frontiers in Pharmacology, 2022)
This study aimed to analyze and discuss the biomarkers of PEGylated-liposomal doxorubicin (PLD) injection-induced hypersensitivity reaction (HSR) in advanced breast cancer patients. Fourteen patients from Sun Yat-sen Memorial Hospital were included in the study between Apr. 15th, 2020 and Apr. 14th, 2021. Patient plasma was collected 30 mins before PLD injection. HSR was found to occur in a total of 9 patients (64.3%). No association was found between HSR and various patient characteristics such as age, body surface area, anthracyclines treatment history, IgE, and Complement 3 and 4 (P>0.05). Non-targeted metabolomics analysis of patient plasma was performed, and several metabolites showed significant association with HSR. In particular, L-histidine (Fold change=91.5, P=0.01) showed significantly higher levels in the immediate HSR group, while myristicin (Fold change=0.218, P=0.003), urocanic acid (Fold change=0.193, P=0.007), and D-Aldose (Fold change=0.343, P=0.003) showed significantly lower levels in the same group. In vivo experiments showed that exogenous histidine aggravated HSR and increased IgE plasma levels in rats following injection of PLD. Histidine can be decarboxylated to histamine by histidine decarboxylase. Histidine decarboxylase inhibitor 4-Bromo-3-hydroxybenzoic acid improved symptoms and IgE levels in vivo. These findings suggested that L-histidine can be a potential biomarker for PLD-induced HSR. Moreover, an anti-histamine drug, histidine decarboxylase inhibitor, or dietary histidine management could be used as potential preventive measures. Furthermore, metabolomics research could serve as a powerful method to explore biomarkers or uncover mechanisms of drug side-effects.